Development and Evaluation of a New Triplex Immunoassay That Detects Group A Streptococcus Antibodies for the Diagnosis of Rheumatic Fever - Whitcombe, Alana L. (J Clin Microbiol, 2020)
Streptococcal serology is a cornerstone in the diagnosis of acute rheumatic fever (ARF), a postinfectious sequela associated with group A Streptococcus infection. Current tests that measure anti-streptolysin O (ASO) and anti-DNaseB (ADB) titers require parallel processing, with their predictive value limited by the low rate of decay in antibody response. Accordingly, our objective was to develop and assess the diagnostic potential of a triplex bead-based assay, which simultaneously quantifies ASO and ADB together with titers for a third antigen, SpnA. Our previous cytometric bead assay was transferred to the clinically appropriate Luminex platform by coupling streptolysin O, DNaseB, and SpnA to spectrally unique magnetic beads. Sera from more than 350 subjects, including 97 ARF patients, were used to validate the assay and explore immunokinetics. Operating parameters demonstrate that the triplex assay produces accurate and reproducible antibody titers which, for ASO and ADB, are highly correlative with existing assay methodology. When ARF patients were stratified by time (days following hospital admission), there was no difference in ASO and ADB between <28 and 28+ day groups. However, for anti-SpnA, there was a significant decrease (P < 0.05) in the 28+ day group, indicative of faster anti-SpnA antibody decay. Anti-SpnA immunokinetics support very recent group A Streptococcus infection and may assist in diagnostic classification of ARF. Further, bead-based assays enable streptococcal serology to be performed efficiently in a high-throughput manner.